Imersifitas Dalam Game Pengenlan Pertumbuhan Kecambah Untuk Anak - Dimas Ikhsan (Informatics Engineering Department-UWKS, 2019)
The development of the gaming industry at the moment is very rapid. Game can be a medium of learning media. One of the most important things that gaming can be an effective learning tool is the game must be interesting and not boring if it is played many times. The immersive nature of the game is a very important factor to make that happen. Researchers want to introduce plants especially Sprouts in different ways and more interesting for children. The lesson that is done for children is still a book containing writing and pictures only. Simulation games that also include plants as game objects are limited to entertainment media only and not learning, such as Harvest Moon and Plant vs. Zombie. Immersive In Game Introduction Growth Sprouts For Children is a game that aims to introduce and attract children to get to know the Sprouts through the immersive side offered, the player must water and grow the plant that begins in the form of seeds to be sprouts like planting a real plant.